Development of a Tabletop Hologram for Spatial Visualization: Application in the Field of Architectural and Urban Design - Tam Le Phuc Do; Matteo Coffin; Philippe Gentet; Leehwan Hwang; Seunghyun Lee (Buildings, 2024)
Architects, engineers, and designers normally visualize architectural, urban planning, urban design, or landscape design projects in different ways to present their ideas. At present, the two most widely utilized and accessible methods for spatial visualization are digital 3D modeling and physical 3D modeling. Despite their popularity, both approaches have intrinsic limitations. These shortcomings are progressively being mitigated through advancements in technology and digitalization. In this study, we propose the utilization of hologram technology as an innovative approach to overcome the limitations of both modeling methods mentioned. This research addresses two main points: the seamless integration of hologram production into the standard workflow of architectural and urban design projects, and the experimental creation of a tabletop hologram prototype using the most advanced stereoscopic visualization capabilities—CHIMERA hologram printer. The experiment’s results indicate that tabletop holograms’ visualization quality can potentially replace traditional methods in the near future. The process of creating holograms can be incorporated into the standard workflow of architectural and urban design projects and utilized in specific contexts.